The role of Actinobacillus actinomycetemcomitans fimbrial adhesin on MMP-8 activity in aggressive periodontitis pathogenesis - Rini Devijanti Ridwan (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2012)
Background: Actinobacillus actinomycetemcomitans (A. actinomycetemcomitans) is Gram negative and a major bacterial agent associated with aggressive periodontitis in young adult, this bacteria was an important factor in pathogenesis of aggressive periodontitis. A. actinomycetemcomitans possesses fimbriae with an adhesin protein that was the first bacterial molecules to make physical contact with host. Purpose: The objective of this research was to analyzed the influence of A. actinomycetemcomitans fimbrial adhesin protein induction on MMP-8 activity. Methods: The research was an experimental laboratory study, the step in this study were isolation and identification A. actinomycetemcomitans, characterize A. actinomycetemcomitans adhesin and study the role of A. actinomycetemcomitans adhesin in Wistar rats. Results: The result of this research on the role of adhesin in Wistar rats after analysis with Analysis of Variance (ANOVA) showed significant differences in the control group with group induction with A. actinomycetemcomitans, A. actinomycetemcomitans plus adhesin and adhesin. MMP-8 activity increased with induction A. actinomycetemcomitans and 24 kDa A. actinomycetemcomitans adhesin. This fimbrial adhesin protein showed that A. actinomycetemcomitans has the ability to adhesion, colonization and invasion for host in aggressive periodontitis pathogenesis. Conclusion: A. actinomycetemcomitans fimbrial adhesin protein induction increasing MMP-8 activity for aggressive periodontitis pathogenesis.Latar belakang: A. actinomycetemcomitans merupakan salah satu bakteri Gram negatif yang terkait dengan periodontitis agresif yang menyerang penderita usia muda dan merupakan faktor penting dalam patogenesis periodontitis agresif. A. actimycetemcomitans mempunyai fimbriae dengan protein adhesin yang merupakan molekul pertama dari bakteri untuk melakukan kontak fisik dengan host. Tujuan: Tujuan penelitian ini adalah menganalisis pengaruh induksi adhesin A. actinomycetemcomitans terhadap aktivitas MMP-8. Metode: Penelitian ini merupakan studi eksperimental laboratori, langkah dari penelitian ini adalah isolasi dan identifikasi A. dan identifikasi A. actinomycetemcomitans, isolasi dan karakterisasi adhesin A. actinomycetemcomitans dan uji peran adhesin A. actinomycetemcomitans di tikus Wistar. Hasil: Hasil analisis menunjukkan adanya aktivitas MMP-8 yang meningkat bermakna di kelompok kontrol dibandingkan dengan kelompok dengan induksi A. actinomycetemcomitans, A. actinomycetemcomitans + adhesin dan adhesin. Hal ini menunjukkan bahwa A. actinomycetemcomitans berkemampuan melakukan adesi, kolonisasi dan invasi pada host dalam patogenesis periodontitis agresif. Kesimpulan: Induksi protein adhesin A. actinomycetemcomitans dengan berat molekul 24 kDa meningkatkan aktivitas MMP-8 pada patogenesis periodontitis agresif.